Identification of guitarfish species Rhinobatos percellens, R. horkelli, and Zapteryx brevirostris (Chondrichthyes) using mitochondrial genes and RFLP technique - Mariguela, T. C. [UNESP]; De-Franco, B. [UNESP]; Almeida, T. V. V. [UNESP]; Mendonca, F. F. [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; Foresti, Fausto [UNESP]; Oliveira, C. [UNESP] (Springer, 2009)
The RFLP represents a fast and non-expensive tool to access species identification and can be used by fishery and law enforcement authorities to gather data from legal and illegal ray fisheries. In the present study, partial sequences of 16S and COI mitochondrial genes were submitted to RFLP analysis and the results showed that there is a high interspecific variability and no intraspecific polymorphism, making them an useful marker for guitarfish identification. All samples of Rhinobatidae: Rhinobatos percellens, R. horkelli, and Zapteryx brevirostris were positively identified. The main contribution of these forensic identification techniques is the possibility of evaluating population genetics of species status in order to improve conservation plans involving these species.
Keywords: Conservation genetics; Mitochondrial genes; Commercial species; Rays; Species identification